Menopause Representations Questionnaire: development and validation with Portuguese women. (4th May 2021) - Albergaria, R.; Leal, I.; Hunter, M.; Pimenta, F.
Abstract: Objective: This study aimed to develop and validate a Portuguese version of the Menopause Representations Questionnaire (MenoSentations-Q), a self-report measure to assess cognitive appraisal of menopause, based on cognitive components of the Self-Regulation Model and the results from a previous Portuguese qualitative study. Methods: A total of 309 Portuguese women, aged 45–65 years, completed the questionnaire. Factorial, convergent, discriminant, and criterion validity, as well as reliability and psychometric sensitivity, were studied. Results: MenoSentations-Q has demonstrated acceptable factorial, convergent, and discriminant validity, as well as good values of sensitivity and reliability for the four factors (i.e. identity; positive consequences; negative consequences; and control, awareness, and cause). Criterion validity was only obtained for two factors. Conclusions: MenoSentations-Q, a brief measure of menopausal representations, in this sample of Portuguese women provides information to inform interventions that might include challenging unhelpful menopausal representations. This instrument could be used in both clinical and community settings.